Modelling price transmission and volatility spillover in the Slovenian wheat market. Issue 41 (2nd September 2017) - Hassouneh, Islam; Serra, Teresa; Bojnec, Štefan; Gil, José M.
ABSTRACT: Interdependence between first and second moments of producer and consumer wheat prices in Slovenia is assessed, in light of the recent major historical events that the country has undergone, as well as the recent rumours of cartel agreements between millers causing a decline in farm-gate prices, while leaving consumer prices untouched. A threshold vector error correction and multivariate generalized autoregressive conditional heteroscedasticity model with exogenous variables is applied. Results indicate that price-level adjustments mainly favour retailers by increasing their marketing margins. Important second-moment interactions are also identified. Increases in international wheat stocks reduce producer prices, while higher interest rates increase their instability.